Effect of risk factors for acneiform rash induced by anti-epidermal growth factor receptor antibody drugs on survival: a retrospective observational study - Hiroaki Takahashi; Yukiko Yaegashi; Yoko Saito; Satoru Nihei; Tomohiko Tairabune; Haruki Ujiie; Junichi Asaka; Kenzo Kudo (BMC, 2022)
Abstract Background We previously reported that high body weight was a risk factor affecting the onset of anti-epidermal growth factor receptor (EGFR) antibody drug-induced acneiform rash. The current study investigated the relationship between risk factors for anti-EGFR antibody drug-induced acneiform rash and survival probability in colorectal cancer patients, as well as effects of drug withdrawal, dose reduction, or treatment discontinuation on treatment continuation. Methods This retrospective study included 67 patients with unresectable advanced or recurrent colorectal cancer treated with anti-EGFR antibody drugs for the first time. Results The survival time and acneiform rash grade of patients with high body weight (≥ 67.2 kg) were significantly longer and higher than those of patients with low body weight (< 67.2 kg). Moreover, the treatment continuation time of patients with drug withdrawal or dose reduction was significantly longer than that of patients without drug withdrawal or dose reduction or with/without treatment discontinuation. Meanwhile, the treatment continuation time of patients with treatment discontinuation was significantly shorter than that of patients with drug withdrawal or dose reduction or those without drug withdrawal, dose reduction, or treatment discontinuation. Conclusions High body weight is a novel prognostic factor for patients receiving cancer drugs with anti-EGFR antibody drugs. Hence, the results of this study suggest that patients with high body weight should be carefully monitored for the development of acneiform rash when receiving anti-EGFR antibody drugs as cancer drug therapy.